Numerical analysis of reinforced concrete beams pre cracked reinforced by composite materials (Fracture and Structural Integrity, 2020)
This work constitutes a contribution to the analysis of the behavior of beams reinforced by composite materials. The analysis was made by a study on concrete elements, and in pre-cracked reinforced concrete then reinforced with carbon fiber fabric bonded in tusi using an epoxy resin. In order to study the influence of the initial state of cracking, one of the beams was reinforced without it being pre-cracked and was compared to a pre-cracked and reinforced beam then to another loaded until rupture without being pre-cracked or reinforced and neither reinforced. the beams were pre-cracked and reinforced in their stretched part and on the lateral part with bands of different dimensions in order to avoid delamination on the one hand and to study the recovery of the composite under the effect of shearing and detachment on the other hand. However, the arrival of these structures brings new scientific problems and in particular the mode of rupture.The aim of this work is to increase the bearing capacity, reduce the deflection and limit the opening of cracks by ensuring better behavior of this element. The results obtained showed that the bonding of composite materials on reinforced concrete structures gave an increase in the ultimate breaking load and a reduction in deformations in concrete and steels.The results of this method coincide perfectly with those from the literature.The reinforcement allowed a significant increase in the breaking load and a reduction in the deflection at break up to 80%. The theoretical model based on the theory of modified reinforced concrete made it possible to predict with good precision the behavior in bending until the ultimate and it would be possible to use the fabric and the epoxy resin for the reinforcement in bending in building site, beams.
Keywords: Reinforced concrete; Pre-cracked beams; Composite materials; FRP plate; Deflection; 3D-FEM; Three point bending